Dietary fish oil replacement by soybean oil: Effect on plasma vitellogenin, sex steroids and ovarian steroidogenesis in Chinese strip‐necked turtles (Mauremys sinensis). (2nd July 2018) - Hong, Meiling; Sheng, Cheng; Li, Na; Li, Weihao; Ding, Li; Wang, Dongmei; Shi, Haitao
Abstract: In order to investigate the effects of dietary fish oil replacement, the turtles ( Mauremys sinensis ) were fed four experimental diets for 10 months: FO (100% fish oil), FSO (70% fish oil and 30% soybean oil), SFO (30% fish oil and 70% soybean oil) and SO (100% soybean oil), sampled at pre‐vitellogenesis, vitellogenesis and post‐vitellogenesis. The results showed that plasma gonadotropin‐releasing hormone (GnRH) levels were the highest at pre‐vitellogenesis, which promoted the secretion of gonadotropin and sex steroids. Therefore, plasma luteinizing hormone (LH) and estrogen (E2 ) levels were significantly increased at post‐vitellogenesis ( p < 0.05), while follicle‐stimulating hormone (FSH) levels increased at vitellogenesis ( p < 0.05). The FO and FSO groups had significantly higher GnRH and E2 levels than the other two groups ( p < 0.05). In addition, plasma vitellogenin (Vtg) levels significantly increased at vitellogenesis and post‐vitellogenesis ( p < 0.05), which were significantly higher in the groups of FO and FSO than SO ( p < 0.05). Moreover, the expression levels of hepatic estrogen receptor α (Erα) mRNA were significantly increased at vitellogenesis and post‐vitellogenesis while ovarian Cyp19α1α mRNA were significantly increased at post‐vitellogenesis ( p < 0.05), and both were the lowest in SO. Taken together, the replacement of fish oil with 66.7% soybean oil is feasible.